Legal Protection of Copyright for Classical Dance Artworks in the Mangkunegaran Style at the Puro Mangkunegaran Surakarta - Adi Nugroho; Aidul Fitriciada Azhari; Wardah Yuspin (Jurnal Hukum dan Kenotariatan, 2024)
Puro Mangkunegaran is one of the fractional kingdoms of the Islamic Mataram Palace which still inherits Javanese cultural customs, one of which is dance culture. This study aims to determine the implementation of copyright protection for the classical dance of the Mangkunegaran Style based on Law Number 28 of 2014 concerning Copyright and the role of local government agencies in the preservation of the Mangkunegaran style classical dance. This research method uses an empirical juridical approach. Sources of data from primary data, namely interviews and secondary data, namely primary and secondary legal sources. Methods of data collection using literature studies and interviews with artists Puro Mangkunegaran and local government agencies. Data analysis is a qualitative approach. The results of this study are that Puro Mangkunegaran itself is quite strong in protecting the classical dance of the Mangkunegaran Style without registering copyright records.